Young people's participation : revisiting youth and inequalities in Europe - Bruselius-Jensen, Maria; Pitti, Ilaria; Tisdall, E. Kay M. (Policy Press, 2021)
This book explores how young people across different European contexts participate in decision-making and foster changes on issues that concern them and their communities, giving new insights into discourses on young people's as active citizens across Europe.